Effectiveness of Exercise with Balloon for Low Back Pain in Young Adults: A quasi experimental study (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2020)
Background: Low back pain is a common musculoskeletal disorder which may be acute, sub acute andchronic in nature. Low back pain is expressed in 42% in adults. Low back pain occurrence is at an early ageand can cause disease progression. Low back pain is due to suboptimal breathing patterns and impairmentsof posture and trunk stability. Many muscles used for the postural control and respiration are same thatis diaphragm, transverses abdominis and muscles comprising the pelvic floor. The diaphragm is the keymuscle for the respiratory pump with attachment from the lower six ribs, xiphoid process of sternum andthe vertebral column. Diaphragm performs both postural and breathing function. Disruption in one functioncould negatively affect the other.Objectives: 1.To find the Effectiveness of 90/90 bridge with ball and balloon exercises and Interferentialtherapy for pain and disability in low back pain among young adults.2. To find the Effectiveness of Interferential therapy for disability and pain in low back pain among youngadults.3. To compare the effectiveness of 90/90 bridge with ball and balloon exercise and Interferential therapytogether and Interferential therapy alone for pain and disability in back pain among young adults.Study Design: A quasi experimental studyMethods: 18 adults who had mechanical low back pain were included in the study. Participants weredivided into 2 groups .Group A received 90/90 bridging with ball and balloon and interferential therapy andGroup B received interferential therapy alone. Exercises were given twice a day for 3 days for 4 weeks. Preand post exercise evaluation is taken by using numerical pain rating scale and Modified Oswestry disabilityindex scale Questionnaire. Data was analyzed using independent T test and paired T test.Result: In both the group there was improvement but there is a significant difference in 90/90 bridge withball and balloon exercise and interferential therapy than the IFT alone among the young adults with lowback pain.Conclusion: This study concludes that there is greater effect of 90/90 bridge with ball and balloon exerciseon patients with mechanical low back pain.
Keywords: Balloon exercises, breathing exercises, low back pain.